Proposal for academic acculturation in the teaching of Epistemology for the Bachelor’s degree of Spanish and Literature (2017)
Introduction: The objective of this article is to describe the phenomenon of academic acculturation with students of the first level of their Bachelor’s Degree in Spanish and Literature of the “Universidad Industrial de Santander” (UIS). In turn, it proposes a didactic sequence adapted to the needs defined in this process of acculturation for the teaching of Epistemology and accompaniment in the development of reading, writing and oral skills; all of this with the aim of reducing desertion levels at university level education. Methodology: This research is mixed with a participatory process methodology. It uses investigative action with a socio-anthropological focus. The theories used are based on the epistemological models of the social sciences, the theories of argumentation, reading, writing and oral skills. Results: It was found that the accompaniment of the teacher, with regards to the tools used and interdisciplinarity nature of the course, help to enhance the acquisition of reading, writing and oral skills in students that, in general, arrive with conceptual and procedural gaps. This process identified, an initial clash of cultures, the implementation of individual strategies and their assimilation. These stages vary from individual to individual and are the “right of passage” required to understand their path through university.